Política fiscal e dívida pública no Brasil: uma análise para o Período 1994 2008 - Santos, Márcio Éder dos [UNESP]; Strachman, Eduardo [UNESP] (My University, 2014)
The paper presents a study of fiscal policy and public debt in Brazil from 1994 to 2008. We assert that fiscal policy in Brazil was conducted in accordance with a new macroeconomic model, and that the measures adopted in that framework resulted in the construction of a new fiscal model. The fiscal policy in this new system has the main role of debt sustainability, with a suitable revenue and spending policy, conducted to achieve the goals of a positive public sector primary result.

O trabalho apresenta um panorama da política fiscal e da dívida pública no Brasil, no período de 1994 a 2008. Afirmamos que a política fiscal, no Brasil, foi conduzida de acordo com o novo modelo macroeconômico e que as medidas adotadas no âmbito da política fiscal resultaram na construção de um novo modelo fiscal, ligado àquele modelo macroeconômico. Coube, à política fiscal, nesse novo modelo macroeconômico, estabelecer metas adequadas de gastos e receitas, de maneira que pudessem ser alcançados resultados primários significativos, capazes de conferir sustentabilidade à dívida pública.
Keywords: Fiscal policy; Fiscal indicators; New fiscal model; Finanças Públicas; Brasil; Economia Pós-Keynesiana; Política Econômica; Política Fiscal; Política Monetár